PERKAWINAN ANTAR NEGARA DI INDONESIA BERDASARKAN HUKUM PERDATA INTERNASIONAL - Siahaan, Hotman (Solusi, 2019)
Marriage is a legal event when the marriage is a legal marriage. The development of science and technology that so rapidly bring the influence on the easier possibility of relations between human beings, between ethnic groups, and between countries in all aspects of life. One of the effects is mixed marriage phenomenon between spouses of different citizenship, including on Indonesian workers with foreign workers. Different nationalities marriage often raises a problem, especially related to the process of marriage registration that will take place, whether in the country of origin of a prospective husband or in the country of origin of a prospective wife. The procedure of mixed nationality marriage according to international civil law explains that marriage rules to different citizen pairs will use either law of the prospective husband’s State or law of the prospective wife’s State. The problems that arise in a mixed nationality marriage procedure are in the process of preparing a certificate from the marriage officer and at the preparing of the letter or other documents. Completion of the problems that arise in mixed marriages procedures that have prepared government is to provide clear information and website to couples who want to get married. For those who do not comply the rules will be imposed a sanction.